Disease activity in chronic inflammatory demyelinating polyneuropathy - Albulaihe, Hana; Alabdali, Majed; Alsulaiman, Abdulla; Abraham, Alon; Breiner, Ari; Barnett, Carolina; Katzberg, Hans D.; Lovblom, Leif E.; Perkins, Bruce A.; Bril, Vera (Journal of the neurological sciences, 2016)
Evaluation of disease status in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) is often done by a combination of clinical evaluation and electrodiagnostic studies. A CIDP disease activity status (CDAS) was developed to standardize outcomes in CIDP patients. We aimed to determine if the CDAS was concordant with classical evaluation and whether CDAS enables benchmarking of CIDP. We performed a retrospective chart review of 305 CIDP patients and identified 206 patients with >1 visit and applied the CDAS to this cohort. We examined relationships between the CDAS and classical evaluation as to outcomes and compared our cohort to other CIDP cohorts who had CDAS. We found that the CDAS mirrored disease severity as measured by electrophysiology and vibration perception thresholds in that CDAS class 5 had more severe neuropathy. Our results are similar to other cohorts in the middle CDAS strata with the exception of fewer subjects in CDAS 1 and more in CDAS 5. The only demographic factor predicting CDAS 5 in our cohort was age, and the overall treatment response rate using the CDAS classification was 79.3%. CDAS appears to have sufficient face-validity as a grading system to assess disease activity in relation to treatment status. The use of CDAS appears to allow benchmarking of patients with CIDP that may be useful in subject selection for clinical trials and also to highlight differences in practice. •CDAS appears to be a valid grading system to assess disease activity.•CIDP patients at CDAS class 5 have more severe neuropathy.•CDAS may be useful in subject selection for clinical trials.